Retrospective analysis of stillbirth at a tertiary care hospital - Gautam, Sarika; Rani, Vandana; Dalal, Monika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Stillbirth is a matter of concern for mother and family as it leads to mental trauma and requires a supportive counselling about the cause of death, management of current pregnancy and future of next pregnancy. Methods: Present retrospective observational study was conducted at a tertiary care hospital over a period of 3 years which include 1765 females who had foetal death. Pregnancy of ≥28 week or fetal weight ≥1000 gram were taken as inclusion criteria. Results: Total number of births in above said period were 32085 and number of total stillbirth reported were 1765 that is 5.5% of total birth. Maximum cases had their first pregnancy (45.3%) and of were of 20 to 25-year age group (61.02%), and most of them were illiterate (63.96%) and belong to low socioeconomic status (95.8%). The causes for stillbirth were divided into four groups - medical, obstetrical, placental and unexplained causes which were 6.96%, 31.38%, 14.10%, and 47.53% respectively. Management of stillbirth was done as per standard protocol for the department and 90.9% cases had vaginal deliveries, 8.8% cases had caesarean section, and 0.16% had operative vaginal delivery. Conclusions: Stillbirth is a hidden component of new born health status which is often neglected when we talk about perinatal mortality and infant mortality. Majority of case had hypertensive disorders of pregnancy followed by antepartum haemorrhage, infection and congenital malformations.